Locust: C++ software for simulation of RF detection. (26th November 2019) - Ashtari Esfahani, A; Böser, S; Buzinsky, N; Cervantes, R; Claessens, C; Viveiros, L de; Fertl, M; Formaggio, J A; Gladstone, L; Guigue, M; Heeger, K M; Johnston, J; et al.
Abstract: The Locust simulation package is a new C++ software tool developed to simulate the measurement of time-varying electromagnetic fields using RF detection techniques. Modularity and flexibility allow for arbitrary input signals, while concurrently supporting tight integration with physics-based simulations as input. External signals driven by the Kassiopeia particle tracking package are discussed, demonstrating conditional feedback between Locust and Kassiopeia during software execution. An application of the simulation to the Project 8 experiment is described. Locust is publicly available at https://github.com/project8/locust_mc .